PEMBENTUKAN KARAKTER SISWA MELALUI PENDIDIKAN AGAMA ISLAM DI SD SAMPEAN TAPANULI SELATAN - Wildan Saleh Siregar (TARBAWI:Journal on Islamic Education, 2022)
Character education is an important discussion in the world of education, this is related to the phenomenon of moral decline that occurs in the midst of an increasingly diverse and increasing society. Character education of students among students is very much needed because character education starts from a young age so that they are used to the future. Therefore, the attitude of responsibility and Islamic religious education at SD NEGERI SAMPEAN must be maximized in shaping character. In this study, the method used is a qualitative approach.This qualitative approach aims to obtain data from symptoms or phenomena about the efforts made by Islamic Religious Education Teachers in shaping the character (character building) of students at SD Sampean Kecamatan Tapanuli Selatan. The program conducts habituation to behave with noble character for teachers at school, provides guidance to students by providing religius guidance that is relevant to character education materials in school.